2014
DOI: 10.1155/2014/617868
|View full text |Cite
|
Sign up to set email alerts
|

Silencing miR-21 Sensitizes Non-Small Cell Lung Cancer A549 Cells to Ionizing Radiation through Inhibition of PI3K/Akt

Abstract: We investigated the role of microRNA-21 (miR-21) in radiotherapy resistance of non-small cell lung cancers (NSCLC) and the underlying molecular mechanism. A549 cells were transfected with anti-miR-21 or the negative control oligonucleotides and real-time PCR was applied to detect miR-21 expression level. After ionizing radiation (IR), the survival fractions, proliferation, apoptosis, and expression of phosphorylated-Akt of A549 cells were determined by clonogenic survival analysis, MTT assay, flow cytometry, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…Thus, effective treatment that sensitizes radioresistant NSCLC to radiotherapy is urgently needed [13]. Recent research has reported that the many miRNAs affect the radiosensitivity of NSCLC cells, which may be associated with apoptosis inhibition [17, 20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, effective treatment that sensitizes radioresistant NSCLC to radiotherapy is urgently needed [13]. Recent research has reported that the many miRNAs affect the radiosensitivity of NSCLC cells, which may be associated with apoptosis inhibition [17, 20].…”
Section: Discussionmentioning
confidence: 99%
“…As an oncomicroRNA involved in tumor progression, microRNA-21-5p (miR-21-5p) is a potential therapeutic target in lung cancer [12]. Overexpression of miR-21-5p has been found in many human malignancies, including NSCLC [13]. For example, high expression of miR-21-5p enhances viability, invasion, viability, and migration of an NSCLC cell line (NCI-H157), and down-regulation of miR-21-5p significantly decreases the levels of certain protein in these cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of miR-21 inhibitors is a strategy that may increase the sensitivity of cancer cells to radiation Ma et al 2014), but its potential impact on surrounding non cancer cells is still unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Long et al demonstrated that ZM447439, a small molecular inhibitor of Aurora-B, induces cell apoptosis and inhibits cell proliferation by decreasing AKT phosphorylation at Ser473 in Hep2 cancer cells (21). Accumulated data has revealed that the PI3K/AKT signaling pathway plays a key role in NSCLC malignant behavior (22)(23)(24). Therefore, it was hypothesized that silencing Aurora-B may decrease the activity of the PI3K/AKT signaling pathway in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%